ANALISIS PENGARUH IKLAN DI MEDIA SOSIAL DAN JENIS MEDIA SOSIAL TERHADAP PEMBENTUKAN PERILAKU KONSUMTIF MAHASISWA DI YOGYAKARTA - Nuning Kristiani (Jurnal Bisnis dan Ekonomi, 2017)
The research is aimed to find out the influence of advertisements in sosial media toward the consumption behavior of the university students in Yogyakarta.The independent variables in this research are advertisements in social media and type of social media, and the dependent variable is the consumptive behavior of the students. The research was conducted by choosing randomly the population of the whole university students in Yogyakarta as respondents using Convenience sampling method. The research resulted two important points. The first is that advertisements in social media influence the consumptive behavior formation of the students in Yogyakarta and second, the type of social media effects the consumptive behavior formation of the students in Yogyakarta. Social media is one of the effective tools to reach the youngsters today. With the abundance of choices and the simple way to make the account, sosial media is simply reachable and accessible among students. Likewise, social media is used as the reference prior buying. In conclusion, this research provides the evidence that advertisement in sosial media effects the consumptive behavior Keywords: advertisements, social media, consumtion behavior